2017
DOI: 10.1111/1751-2980.12459
|View full text |Cite
|
Sign up to set email alerts
|

Nonvariceal upper gastrointestinal bleeding in elderly people: Clinical outcomes and prognostic factors

Abstract: Clinical evolution and mortality do not differ between the elderly and younger patients with acute nonvariceal UGIB. Serum albumin level at admission is a prognostic marker for mortality in elder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…[1] The incidence of NVUGIH is 20-60/100,000 people, [24] and is particularly high among elderly patients who carry other types of systemic diseases; the mortality rate in these patients is about 7% to 14%. [5] The prognosis of upper gastrointestinal bleeding may vary from mild to life- threatening. [4] Patients with mild bleeding might fully recover without specific clinical treatment, while those with severe bleeding may experience severe complication and even death if they do not receive the treatment for the condition.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The incidence of NVUGIH is 20-60/100,000 people, [24] and is particularly high among elderly patients who carry other types of systemic diseases; the mortality rate in these patients is about 7% to 14%. [5] The prognosis of upper gastrointestinal bleeding may vary from mild to life- threatening. [4] Patients with mild bleeding might fully recover without specific clinical treatment, while those with severe bleeding may experience severe complication and even death if they do not receive the treatment for the condition.…”
Section: Introductionmentioning
confidence: 99%
“…As in Western populations, the proportion of elderly people in Turkey has increased (1). As life expectancy has increased, so have the comorbidities and the use of medications such as acetylsalicylic acid, nonsteroidal anti-inflammatory drugs (NSAIDs), and oral anticoagulants (2). Despite the decline in incidence of NVUGB and the advances in diagnostic procedures, resuscitation, medical and endoscopic treatment, and intensive care, the rate of mortality remains unchanged (3).…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the albumin level has also been verified in the context of the management of gastrointestinal bleeding patients. Gonzalez-Gonzalez et al reported a correlation ( p = 0.001, OR 5.230, 95% CI 2.099–13.029) with the prognosis of serum albumin values in elderly peptic ulcer patients; thus, the albumin level may be useful as a prognostic marker [ 18 ].…”
Section: Discussionmentioning
confidence: 99%